Characteristics of paediatric weight management in the United States: Associations with program retention and BMI outcomes in the paediatric obesity weight evaluation registry (POWER). Issue 2 (9th September 2021) - Tucker, Jared M.; Stratbucker, William; King, Eileen C.; Cuda, Suzanne; Negrete, Sylvia; Sweeney, Brooke; Kumar, Seema; Borzutzky, Claudia; Binns, Helen J.; Kirk, Shelley; ,
Summary: Objective: To describe characteristics of paediatric weight management (PWM) programs across the United States and evaluate associations with program‐specific retention rates and body mass index (BMI) outcomes at 6 months. Methods: A program profile survey was administered to 33 programs within the Paediatric Obesity Weight Evaluation Registry (POWER) to assess program staffing, services, and treatment format. Patient retention and percent of the 95th BMI percentile (%BMIp95) changes were assessed for each program. Results: At 6 months program retention rates ranged from 15% to 74% (median: 41%), and program %BMIp95 changes ranged from −9.0 to +0.5 percentage points (median: −1.7). Percent of patients with ≥5 percentage‐point decrease in %BMIp95 ranged from 17% to 71% across programs (median: 29%). No associations were detected between program characteristics and retention or %BMIp95 changes. Conclusions: Six‐month patient retention and BMI outcomes vary substantially in PWM programs across the United States. Yet, no associations were found between PWM treatment factors and these program‐level patient outcomes.